2004
DOI: 10.1136/bjsm.2003.010298
|View full text |Cite
|
Sign up to set email alerts
|

Self reported injury patterns among competitive curlers in the United States: a preliminary investigation into the epidemiology of curling injuries

Abstract: Objective: To investigate the injury patterns among competitive curlers. Methods: Participants at two curling championship events were asked to complete injury history questionnaires. Results: 76 curlers (39%) participated; 79% of these reported curling related musculoskeletal pain, most commonly involving the knee (54%), back (33%), and shoulder (20%). Sweeping and delivering the stone were most likely to provoke symptoms. Time loss injuries were estimated to occur at a rate of 2 per 1000 athlete exposures.Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
1
15
0
2
Order By: Relevance
“…Following release of the stone, the curler continues sliding forward to monitor the stone's path while maintaining extreme hip and knee flexion on the athlete's nondominant, nondelivery side (Reeser & Berg, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Following release of the stone, the curler continues sliding forward to monitor the stone's path while maintaining extreme hip and knee flexion on the athlete's nondominant, nondelivery side (Reeser & Berg, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Le curling est devenu un sport olympique officiel lors des Jeux olympiques d'hiver de 1998. Bien que la Fédération mondiale de curling compte 49 pays membres, les Canadiens représentent environ 80 % de la population de joueurs de curling dans le monde, avec une population de joueurs variant entre 730 000 et 870 000 adeptes 1,2,4 . Malgré cela, il y a très peu de données publiées concernant la fréquence des blessures.…”
Section: Introductionunclassified
“…Une étude axée sur les deux championnats nationaux a révélé que le taux autodéclaré de blessures graves entraînant une « perte de temps », ce qui caractérise l'exposition de l'athlète, était de 2 à 2,3 par 1 000 parties jouées 4 . Lors d'un autre championnat masculin, le taux autodéclaré de blessures graves a été de 3,5 par 1 000 athlètes exposés 6 .…”
Section: Introductionunclassified
“…Although the World Curling Federation comprises 49 member countries, Canadians make up about 80% of the worldwide curling population, with between 730 000 and 870 000 curlers. 1,2,4 Yet there is little published information on occurrence of injuries.…”
Section: Introductionmentioning
confidence: 99%
“…One study that focused on two national championships found that acute injuries resulting in ''time loss,'' or athlete-exposures (AEs), occurred at a self-reported rate of 2 to 2.3 per 1000 games. 4 At another men's championship, acute injuries occurred at a self-reported rate of 3.5 per 1000 AEs. 6 At the 2010 Winter Olympics, the acute injury rate requiring medical attention was 2.5 per 1000 AEs; the two acute injuries happened to men while the women's bracket reported no injuries.…”
Section: Introductionmentioning
confidence: 99%